2018
DOI: 10.3354/dao03255
|View full text |Cite
|
Sign up to set email alerts
|

Edwardsiella ictaluri type III secretion system (T3SS) effector EseN is a phosphothreonine lyase that inactivates ERK1/2

Abstract: EseN is a type III secretion system (T3SS) effector that is encoded on the Edwardsiella ictaluri chromosome and is homologous to a family of T3SS effector proteins with phosphothreonine lyase (PTL) activity, including OspF from Shigella and SpvC from Salmonella. A yeast-2-hybrid system was used to identify the major vault protein (MVP) as a specific host-cell binding partner for EseN, and the proximity ligation assay (PLA) confirmed the interaction. Similar to other pathogens, E. ictaluri invasion activates ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…In contrast, transcription and assembly of the related Salmonella SPI-2 T3SS only requires acidification of the SCV [ 104 ]. The EseN effector plays an important role in E. ictaluri invasion, where it activates extracellular replication in catfish head kidney by dephosphorylation in vivo in the head kidney of infected fish, and ex vivo in macrophages derived from the head kidney [ 105 ]. EseN can also shut down signal-regulated kinases 1 and 2 (ERK1/2) early in the infectious process [ 80 , 105 ].…”
Section: T3ss In Aquatic Pathogensmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, transcription and assembly of the related Salmonella SPI-2 T3SS only requires acidification of the SCV [ 104 ]. The EseN effector plays an important role in E. ictaluri invasion, where it activates extracellular replication in catfish head kidney by dephosphorylation in vivo in the head kidney of infected fish, and ex vivo in macrophages derived from the head kidney [ 105 ]. EseN can also shut down signal-regulated kinases 1 and 2 (ERK1/2) early in the infectious process [ 80 , 105 ].…”
Section: T3ss In Aquatic Pathogensmentioning
confidence: 99%
“…The EseN effector plays an important role in E. ictaluri invasion, where it activates extracellular replication in catfish head kidney by dephosphorylation in vivo in the head kidney of infected fish, and ex vivo in macrophages derived from the head kidney [ 105 ]. EseN can also shut down signal-regulated kinases 1 and 2 (ERK1/2) early in the infectious process [ 80 , 105 ]. Furthermore, there is evidence of reduced numbers of bacteria in infected tissue and in mortality in channel catfish ( Ictalurus punctatus ) infected with bacteria with a deleted eseN gene bacteria compared to wild-type infected tissue [ 105 ].…”
Section: T3ss In Aquatic Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that in many pathogens secreted effectors can affect intracellular uptake, surface colonization of the cell without uptake, adherence to macrophages and inhibition of phagocytosis, cytotoxicity, vesicular trafficking, control of programmed cell death, manipulation of gene expression, and up- and down-regulation of inflammatory cytokines [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. The E. ictaluri effector EseN is a phosphothreonine lyase (PTL) that inactivates extracellular mitogen-activated protein kinases (ERK1/2) [ 12 ]. Based on similarity to other effectors, EseN can also inactivate other mitogen-activated-protein-kinases (MAPKs) [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because EseN is important for the virulence of E. ictaluri [ 2 , 12 ] and the virulence mechanisms of this factor are unknown, RNAseq and transcriptome analysis were used to identify potential genes and pathways that are modulated by EseN. We used RT-qPCR to confirm RNAseq data and to study extended time points of infection.…”
Section: Introductionmentioning
confidence: 99%